Identification of AKR1B10 as a key gene in primary biliary cholangitis by integrated bioinformatics analysis and experimental validation - Wang, Huiwen; Zhang, Jian; Liu, Jinqing; Jiang, Yongfang; Fu, Lei; Peng, Shifang (Frontiers in Molecular Biosciences, 2023)
Background: Primary biliary cholangitis (PBC) is a chronic autoimmune liver disease that eventually progresses to cirrhosis and hepatocellular carcinoma (HCC) in the absence of proper treatment. However, Gene expression and molecular mechanisms involved in the pathogenesis of PBC has not been completely elucidated. Methods: Microarray expression profiling dataset GSE61260 was downloaded from the Gene Expression Omnibus (GEO) database. Data were normalized to screen differentially expressed genes (DEGs) using the limma package in R. Moreover, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes pathway (KEGG) enrichment analyses were performed. A protein–protein interaction (PPI) network was constructed to identify hub genes and an integrative regulatory network of transcriptional factor–DEG–microRNA was established. Gene Set Enrichment Analysis (GSEA) was used to analyze differences in biological states for groups with different expressions of aldo-keto reductase family 1 member B10 (AKR1B10). Immunohistochemistry (IHC) analysis was performed to validate the expression of hepatic AKR1B10 in patients with PBC. The association of hepatic AKR1B10 levels with clinical parameters was evaluated using one-way analysis of variance (ANOVA) and Pearson’s correlation analysis. Results: This study identified 22 upregulated and 12 downregulated DEGs between patients with PBC and healthy controls. GO and KEGG analysis revealed that DEGs were mainly enriched in immune reactions. AKR1B10 was identified as a key gene and was further analyzed by screening out hub genes from the PPI network. GSEA analysis indicated that high expression of AKR1B10 might promote PBC to develop into HCC. Immunohistochemistry results verified the increased expression of hepatic AKR1B10 in patients with PBC and demonstrated its positive correlation with the severity of PBC. Conclusion: Integrated bioinformatics analysis and clinical validation was used to identify AKR1B10. The selective increase of AKR1B10 expression in patients with PBC was associated with disease severity and might promote the progression of PBC to HCC.